Jumpstart! creativity games and activities for ages 7-14 - Bowkett, Stephen (Routledge, 2018)
"Jumpstart! Creativity contains over 70 games and activities that any primary teacher can use to quickly and easily boost students' creative and critical thinking skills, allowing their thinking to flourish. Now in its second edition, the book contains fresh material that will help children to engage with the new National Curriculum. Applicable across a wide age and ability range, Jumpstart! Creativity is designed to help children learn to generate, organise and refine their own ideas and to explore, question and connect knowledge presented to them in the classroom. Focusing on getting the children to do the thinking work, the jumpstarts cover: Creative thinking; Creative questioning; Creating reasoning; Creative problem solving; Creative wordplay. Filled with practical, fun-packed and easy-to-do activities, Jumpstart! Creativity is an essential companion to any primary teacher looking to inspire creativity and independent thinking in their students"--The publisher.